Proceedings of the Sixth International Conference on Learning Analytics &Amp; Knowledge 2016
DOI: 10.1145/2883851.2883935
|View full text |Cite
|
Sign up to set email alerts
|

Data-driven proficiency profiling

Abstract: Data-driven methods have previously been used in intelligent tutoring systems to improve student learning outcomes and predict student learning methods. We have been incorporating data-driven methods for feedback and problem selection into Deep Thought, a logic tutor where students practice constructing deductive logic proofs. In this latest study we have implemented our data-driven proficiency profiler (DDPP) into Deep Thought as a proof of concept. The DDPP determines student proficiency without expert invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…This work assesses the impact of incorporating hint usage in predicting student behavior. While researchers have extensively explored predictive student modeling tasks such as predicting student performance (Wang and Heffernan 2011;Chaudhry et al 2018), problem selection (Mostafavi et al 2015), and adaptive assistance (Conati et al 2002), less attention has been paid to the role of students' hint usage in such modeling tasks. The work by Beck et al (2004) was one of the first to assess the impact of tutor help on predictive modeling.…”
Section: Hint Usage In Student Modelingmentioning
confidence: 99%
“…This work assesses the impact of incorporating hint usage in predicting student behavior. While researchers have extensively explored predictive student modeling tasks such as predicting student performance (Wang and Heffernan 2011;Chaudhry et al 2018), problem selection (Mostafavi et al 2015), and adaptive assistance (Conati et al 2002), less attention has been paid to the role of students' hint usage in such modeling tasks. The work by Beck et al (2004) was one of the first to assess the impact of tutor help on predictive modeling.…”
Section: Hint Usage In Student Modelingmentioning
confidence: 99%
“…However, as highlighted by recent reports, such tools may provide little added value on their own. To be effective, they must be well implemented and well integrated into the broader system (Lipsky 2010;Mostafavi, Liu, and Barnes 2015). Ultimately, the success of such tools depends on their adoption by the counselors (Lipsky 2010).…”
Section: Algorithmic Decision-making Long-term Unemployment and Human Detachment And Attachment To Decision-makingmentioning
confidence: 99%
“…For example, a study of Poland's PES system revealed that case counselors are not always transparent about the use of the profiling system with the unemployed (Sztandar-Sztanderska and Zielenska 2018). Several studies analyzed the effectiveness of profiling systems (Lipsky 2010;Mostafavi, Liu, and Barnes 2015;Weber 2011) and how profiling tools are used by counselors in practice (Weber 2011;Sztandar-Sztanderska and Zielenska 2018). However, while the extant scholarly work shows that frontline employees struggle to use the systems that employ AMD with poorly implemented off-the-shelf software interfaces (e.g., Raso 2017), the evidence base is still weak and arguably incomplete.…”
Section: Algorithmic Decision-making Long-term Unemployment and Human Detachment And Attachment To Decision-makingmentioning
confidence: 99%
“…Deep Thought (DT, Figure 1) is an intelligent tutor for solving open-ended multi-step propositional logic problems that has data-driven features including next-step hints [8,75], as well as adaptive problem selection [51,53] and ped-Fig. 2: A sample solution of a training problem in Deep Thought agogical policies for worked example presentation induced via reinforcement learning [6,52,72,73].…”
Section: System Designmentioning
confidence: 99%